Dynamic enzymatic kinetic resolution of NSAIDS - Kamaruddin, A.; Uzir, M.; Gonawan, F.; Lau, John (2015)
© Springer International Publishing Switzerland 2015. The optical purity of non-steriodal anti-inflammatory drugs (NSAIDs) is one of the concerns in pharmaceutical industries, since the enantiomers demonstrate distinct physical and chemical characters. The production of single enantiomer of NSAIDs through dynamic enzymatic kinetic resolution (DEKR) has been pinpointed as among the promising approach developed in recent years. The substrate conversion and product enantioselectivity could be improved as compared to the conventional kinetic resolution. A combination of enzymatic kinetic resolution (EKR) and base-catalyzed racemization process can guarantee racemic substrate conversion of more than 80%. The utilization of hollow-fiber membrane as enzyme-mediated reactor significantly improves the DEKR operation. This chapter describes the DEKR of a racemic ibuprofen in enzymatic membrane reactor (EMR), which system has been intensively investigated. From the experimental work, high conversion of the substrate (>90%) and opticaly pure product (ee P >95%) have been obtained. The kinetic model was integrated with that of the mass transfer in the cylindrical hollow-fiber module in order to simulating the entire system by the interaction between the EKR and racemization reaction. The product ((S)-ibuprofen acid) was crystallized and the preliminary toxicity studies were carried out. In conclusion, DEKR of NSAIDs is a promising technology for the production a single enantiomer of NSAIDs.